PENGARUH SELF ASSESSMENT SYSTEM TERHADAP PENERIMAAN PAJAK PERTAMBAHAN NILAI PADA PENGUSAHA KENA PAJAK ( Studi Kasus pada KPP Pratama Semarang Candisari ) (Students' Journal of Accounting and Banking, 2014)
The study was conducted to analyze the influence of the number of registered PKP, the amount of SSP PPN and the number of reported SPT Masa PPN for PPN receipts. The study object is the KPP Candisari Semarang period 2008-2012.The data analysis technique used is multiple linear regression equation. Data collection techniques used were documentation studies was the number of registered PKP, the amount of SSP PPN and the number of reported SPT Masa PPN and PPN receipts period 2008-2012 (sensus).The results of this study indicate that of the number of registered PKP, the amount of SSP PPN variables showed no significant effect on PPN receipts.Variable such as the number of times the reported SPT Masa PPN significant positive effect on PPN receipts.Keywords: the number of registered PKP, the amount of SSP PPN and the number of reported SPT Masa PPN and PPN receipts